(untitled) (Global Journal of Medical Research, 2020)
We present the clinical case of a 23-year-old male patient with a history of heart transplantation who suffered a bicycle accident presenting a bloody area in the left tibial region which was subjected to taking and applying a skin graft and allograft placement in a donor area under sedation. And ultrasound-guided femoral nerve block without presenting hemodynamic changes during the trans-anesthetic and adequate analgesia, resulting in a very useful alternative for this type of patients since they present physiologicalanatomical changes after transplantation and it is required to maintain a hemodynamic state optimal to avoid peri operative complications.